1D trilayer films grating with W/SiO2/W structure as a wavelength-selective emitter for thermophotovoltaic applications. (June 2015) - Song, Jinlin; Wu, Hao; Cheng, Qiang; Zhao, Junming
Abstract: Wavelength selectivity of emitters is of great importance for thermophotovoltaic applications. In this paper, a modified 1D trilayer films grating with a silica (SiO2 ) layer sandwiched between two tungsten (W) layers to form the W/SiO2 /W structure is proposed to obtain high spectral selective emittance. High average emittance of 0.95 is obtained for TM waves from about 600 nm to 1900 nm, and a broadband emission peak with emittance close to unity occurs between 900 nm and 1800 nm. Simultaneously, the emittance decreases sharply when λ >1800 nm, which can minimize the thermal loss. The finite-difference time-domain method (FDTD) is utilized to analyze the radiative properties of the grating. The inductance–capacitance (LC) circuit model for this trilayer grating structure is presented to predict the magnetic polaritons (MPs) resonance location compared with the results obtained by FDTD method. The effects of the geometric parameters and emission angles on the emittance of the proposed grating are also investigated. The broadband emittance peak is considered as the combined results of the surface plasmon polaritons (SPPs) and several fundamental modes of magnetic polaritons (MPs) resonance at neighboring wavelengths. Highlights: A novel 1D trilayer films grating as a broadband emitter is proposed. The LC circuit model is applied to calculate the magnetic resonance wavelength. The effects of geometric parameters and emission angles are investigated. The broadband emission peak is attributed to the interaction of the SPPs and MPs.